Comparative Analysis Of Financial Risk Management And Its Effects On Earnings (Case Study Of PT Bank Muammalat Indonesia, PT Bank Syariah Mandiri, And PT Bank BNI Syariah). - Laili Maghfiroh Inayati (IE 13 UMY 237, 2013)
This thesis entitled "comparative analysis of financial risk management and its effects on earnings (case study of pt bank muammalat indonesia, pt bank syariah mandiri, and pt bank bni syariah) 2008-2012". Is to identify the factors that influence the risk of financing in Islamic banking in Indonesia, to identify and analyze the financial risk management in Islamic banking in Indonesia, analyze the development of financing, NPF, and profit on Islamic banking in Indonesia, analyze the effect of financing and NPF to profit on Islamic banking in Indonesia. The factors that influence the risk of financing come from internal and external. Internal factors are human resources, information technology, policies and procedures. and external factors are debtors , government policy , and competition with other banks . This study uses multiple linear regression analysis using eviews 7. The finding shows that financing has impacts on earning and NPF on Islamic banking in Industry Keywords: profit, finance, NPF